The Effect Of Organizational Culture, Work Discipline, Quality Of Human Resources In Increasing Motivation - Hery Fadley (CV. Eureka Murakabi Abadi, 2023)
This study aimed to find out how much the effect of organizational culture, work discipline, quality of human resources in increasing motivation. This study used a quantitative method. This research was conducted in 6 (six) District offices, namely, Batang, Tarowang, Kelara, Arungkeke, Binamu, Turatea Districts. The research population was all employees in 6 (six) sub-district offices, a total of 113 people. Using a probability sampling technique, the questionnaire distribution was carried out in stages, where all respondents completed the questionnaire completely. The final sample in the study was 113 people. the procedure for collecting information is the distribution of questionnaires then filled in according to the questions that have been provided. information analysis using path analysis or path analysis with SPSS software version 25.0. The results showed that the direct effect of motivation on employee performance had the highest correlation value compared to other direct effects. Motivation possessed by employees is considered as a personal advantage of employees who are able to provide benefits to agencies because with these abilities individual characters are measurable which makes it easier for management to capture potentials in increasing agency goals. It can be concluded that there is an effect of organizational culture, work discipline, quality of human resources in increasing motivation.